Antigen processing defects in cervical carcinomas limit the presentation of a CTL epitope from human papillomavirus 16 E6. - Evans, M; Borysiewicz, L; Evans, A; Rowe, M; Jones, M; Gileadi, U; Cerundolo, V; Man, S (2001)
Human papillomavirus (HPV) infection, particularly type 16, is causally associated with the development of cervical cancer. The E6 and E7 proteins of HPV are constitutively expressed in cervical carcinoma cells making them attractive targets for CTL-based immunotherapy. However, few studies have addressed whether cervical carcinomas can process and present HPV E6/E7-derived Ags for recognition by CTL. We generated HLA-A*0201-restricted CTL clones against HPV16 E6(29-38) that recognized HPV16 E6 Ags transfected into B lymphoblastoid cells. These CTL were unable to recognize HLA-A*0201(+) HPV16 E6(+) cervical carcinoma cell lines even when the level of endogenous HPV16 E6 in these cells was increased by transfection. This defect in presentation of HPV16 E6(29-38) correlated with low level expression of HLA class I, proteasome subunits low molecular mass protein 2 and 7, and the transporter proteins TAP1 and TAP2 in the cervical carcinoma cell lines. The expression of all of these proteins could be up-regulated by IFN-gamma, but this was insufficient for CTL recognition unless the level of HPV16 E6 Ag was also increased by transfection. CTL recognition of the HPV16 E6(29-38) epitope in 721.174 B cells was dependent on TAP expression but independent of immunoproteasome expression. Collectively, these findings suggest that presentation of the HPV16 E6(29-38) epitope in cervical carcinoma cell lines is limited both by the level of TAP expression and by the low level or availability of the source HPV E6 oncoprotein. These observations place constraints on the use of this, and potentially other, HPV-derived CTL epitopes for the immunotherapy of cervical cancer.